Determination of force in single cable plane prestressed concrete polygonal line tower cable-stayed bridge based on minimum bending energy - Li, Yanfeng; Guo, Tianyu; Bao, Longsheng; Wang, Fuchun (Archives of Civil Engineering, 2021)
The cable force of a cable-stayed bridge plays a vital role in its internal force state. Different cable forces on both sides of the main tower make the force characteristics of the polygonal-line tower quite different from those of the straight-line tower. Therefore, the determination of the cable force of the polygonal-line tower cable-stayed bridge is a crucial aspect of any evaluation of its mechanical characteristics. A single-cable plane prestressed concrete broken-line tower cable-stayed bridge is taken as a case study to conduct a model test and theoretical cable force determination. The reasonable cable force of the bridge is determined by the minimum bending energy method combined with false load and internal force balance methods. analysis includes a comparison between cable force calculation results, model test results, and the design value of the actual bridge. The distribution law of the dead load cable force of the completed bridge is determined accordingly.
Keywords: cable-stayed bridge; polygonal tower; finite element method; minimum bending energy method